Hints for a General Understanding of the Epitaxial Rules for van der Waals Epitaxy from Ge‐Sb‐Te Alloys. Issue 9 (6th February 2022) - Arciprete, Fabrizio; Boschker, Jos Emiel; Cecchi, Stefano; Zallo, Eugenio; Bragaglia, Valeria; Calarco, Raffaella
Abstract: In this study, a generalized guideline is identified to predict the interaction between two‐dimensional (2D) layered materials and substrate surfaces. Additionally, the van der Waals (vdW) heterostructures commensurability, the phase formation and the strain relaxation are identified during interface growth. To achieve such a general overview, the case of Ge‐Sb‐Te (GST) alloys on InAs(111) is studied. In this system, low‐lattice mismatch conditions are fulfilled to avoid relaxation due to formation of misfit dislocations and allow to correctly identify vdW epitaxy. At the same time, the substrate can be efficiently prepared into self‐ and un‐passivated surfaces to clarify the role of the surface interaction. Furthermore, the GST epilayer exhibits two different highly ordered 2D structures and a three‐dimensional disordered structure, allowing to directly infer the nature of the epitaxy. This study opens the way for the design and mastering of vdW epitaxial growth of 2D heterostructures as well as hybrid 2D and non‐layered materials. Abstract : Van der Waals (vdW) epitaxy represents a powerful way for growing heterostructures made of stacked sequences of 2D crystals, potentially exhibiting new phenomena and peculiar properties. The Ge‐Sb‐Te (GST) alloys are phase‐change materials, widely studied for their applications in memories and neuromorphic devices. In this study, the key parameters to predict the interaction between GST layered materials and substrate surface are identified in order to contribute to a generalized guideline for the design and mastering of vdW epitaxy of 2D materials.